p53 Expression Induces Apoptosis in Hippocampal Pyramidal Neuron Cultures - Jordán, Joaquín (J Neurosci, 1997)
The tumor suppressor gene p53 has been implicated in the induction of apoptosis in dividing cells. We now show that overexpression of p53 using an adenoviral vector in cultured rat hippocampal pyramidal neurons causes widespread neuronal death with features typical of apoptosis. p53 overexpression did not induce p21, bax, or mdm2 in neurons. X-irradiation of hippocampal neurons induced p53 immunoreactivity and cell death associated with features typical of apoptosis. Overexpression of a constitutively active nonphosphorylatable form of the retinoblastoma gene product blocked x-irradiation-induced neuronal death. However, overexpression of the cyclin-dependent kinase inhibitor p21 did not. Treatment of neurons with transforming growth factor-β1 protected them from x-irradiation. These results are consistent with a role for p53 in nerve cell death that is distinct from its actions relating to cell cycle arrest.